Desenvolvimento de um sistema de informações georreferenciadas de segurança viária - Chaves, Mariana Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The analysis and visualization of spatial data have become important in the decision-making process, both for the institutions and for individuals. The data related to road accident occurrence has been published in tabular form and they have rarely been geo-referenced whose form is well suitable for spatial visualization. In Brazil road transportation has been widely used. However, the infrastructure does not meet the demand for quality and safety and then accident´s rates concern the whole society and also the transport security managers. The road accident causative factors are the conditions of the road, the weather, the vehicle, and the driver. Good engineering projects, effective law and its reinforcement, and the triad education, culture and general and scientific information can help minimize the risks of road accidents. Besides projecting, constructing, and maintaining safe roads, the engineers are responsible for the road safety management, among other duties, for what they demand the statistical data of accidents to be properly treated and analyzed. There is here a piece of effective contribution of cartographic engineering for a geographical construction of social interest. The cartographic sciences, plus the geographic information systems (GIS), can contribute to the georeferenced information production related to critical sectors of the roads so as to serve as an aid for both authorities (institutionally) and conductors (individual level) in their decision-making process. Building a geospatial database of traffic accidents is an essential support for understanding the spatial distribution of these events that are demanding a scientific analysis. This thesis presents the development of the research project from the conception until the implementation of the WebSIG/SV...

A análise e a visualização dos dados espaciais tornaram-se importantes no processo de tomada de decisões, tanto para as instituições quanto para os indivíduos. Um tipo de dado passível de visualização espacial é a ocorrência de acidente rodoviário, que tem sido divulgado na forma textual (tabelas) e raramente georreferenciado. O transporte rodoviário é o mais utilizado no Brasil. Todavia, a infraestrutura não atende a demanda com qualidade e segurança e os índices de acidentes viários preocupam a sociedade em geral e também os gestores de segurança em transportes. Os fatores causadores de sinistros viários são as condições da rodovia, da meteorologia, do veículo e do condutor. Bons projetos de engenharia, legislação e fiscalização eficazes, e a tríade educação, cultura e informação geral e científica podem ajudar a minimizar os riscos dos acidentes. Ao engenheiro, além de projetar, executar e manter vias adequadas, compete a gestão da segurança viária, que compreende ações de coleta e tratamento estatístico dos dados de acidentes, entre outras. Vislumbra-se aqui uma parcela de efetiva contribuição da Engenharia Cartográfica para uma construção geográfica de interesse social. As ciências cartográficas, aliadas aos sistemas de informações geográficas (SIG), podem contribuir com a produção de informações georreferenciadas nos trechos críticos das rodovias, de modo a servir de auxílio ao processo de tomada de decisão das autoridades (nível institucional) e dos condutores (nível individual). Construir um banco de dados geoespaciais de acidentes rodoviários de trânsito é um suporte essencial para a compreensão da distribuição espacial desses eventos que estão a exigir uma análise científica. Essa dissertação apresenta o desenvolvimento da pesquisa desde a concepção até a implementação do WebSIG/SV...
Keywords: Cartografia; Sistema viario; Sistemas de informação geografica; Mapeamento digital; Cartography